'What is professional ethics?'. (March 2014) - Brecher, Bob
The very term 'professional ethics' is puzzling with respect to what both 'professional' and 'ethics' might mean. I argue (1) that professionalism is ambiguous as to whether or not it is implicitly committed to ethical practice; (2) that to be 'professionally' ethical is at best ambiguous, if not in fact bizarre; and (3) that, taken together, these considerations suggest that professional ethics is something to be avoided rather than lauded.